KINERJA PEGAWAI PADA FAKULTAS MATEMATIKA DAN ILMU PENGETAHUAN ALAM UNIVERSITAS TADULAKO PALU - Syaharuddin Syaharuddin (Katalogis, 2016)
This study aims to analyze the performance of employees in providing academic services to students. The concept used in this study to examine determinants of employee performance based Theory Handoko namely Efficiency and Effectiveness. This study used a technique informants purposively selecting the number of informants set at 6 Data collection techniques are observation, interviews, and documentation. The results showed that the performance in providing academic services to students Mathematics and Natural viewed from the aspect of efficiency include the understanding and control of the task is not yet fully understood, while the effectiveness seen aspects of the service provided is still not maximized evidenced by the presence of complaints from students due to the unfamiliarity of employees. While the factors inhibiting the performance of employees in academic services are; a culture which is reflected in the behavior of employees, measured from the internal side of employee work ethic, motivation, discipline and the level of dependence of employees on the leadership which is still very high and the external side of the employee interaction pattern that exists in providing services professional